A Crown‐Shaped Ru‐Substituted Arsenotungstate for Selective Oxidation of Sulfides with Hydrogen Peroxide. Issue 43 (3rd July 2018) - Han, Mengdan; Niu, Yanjun; Wan, Rong; Xu, Qiaofei; Lu, Jingkun; Ma, Pengtao; Zhang, Chao; Niu, Jingyang; Wang, Jingping
Abstract: An acetate‐bridged Ru‐substituted arsenotungstate [H2 N(CH3 )2 ]14 [As4 W40 O140 {Ru2 (CH3 COO)}2 ]⋅ 22 H2 O (1 ) has been synthesized and structurally characterized. Four Ru atoms occupy the respective lacunary S2 sites of the crown‐shaped polyanion [As4 W40 O140 ] 28−, and each Ru atom is coordinated by one As atom and five μ2 ‐O atoms, comprising four from the S2 site and one from the acetate ligand. To the best of our knowledge, this coordination of the Ru atom, with an Ru−As bond length of 2.377(3)–2.387(3) Å, is unprecedented in polyoxometalate (POM) chemistry. Notably, 1 exhibits high efficiency, excellent selectivity, and good recyclability for the oxidation of sulfides with hydrogen peroxide (H2 O2 ). Catalytic oxidation of various sulfides in the presence of1 gives superior conversion and selectivity for sulfones in acetonitrile, whereas sulfoxides are obtained in methanol. Abstract : Sulfoxidation : A crown‐shaped Ru‐substituted arsenotungstate [H2 N(CH3 )2 ]14 [As4 W40 O140 {Ru2 (CH3 COO)}2 ]⋅22 H2 O (1 ) has been prepared by a self‐assembly strategy. The catalytic activity of1 towards the selective oxidation of sulfides has been systematically probed (see scheme).